2005
DOI: 10.1001/archinte.165.10.1185
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Characteristics of Stroke Events in the Atrial Fibrillation Follow-up Investigation of Sinus Rhythm Management (AFFIRM) Study

Abstract: In the AFFIRM Study, stroke rates were not significantly different in the rate control and sinus rhythm control arms. However, several clinical and therapeutic variables were associated with stroke risk. In patients with a history of AF at high risk for stroke or death, the presence of AF increases the risk of having a stroke, and warfarin therapy reduces the risk of having a stroke. The beneficial effect of warfarin therapy is seen not only in patients in AF but also in patients with a history of AF but who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(56 citation statements)
references
References 25 publications
0
54
0
2
Order By: Relevance
“…A separate search of the literature was undertaken to identify additional evidence related to the prognostic value of NSR in patients with AF. The search identified an analysis of the AFFIRM study, which examined the occurrence and characteristics of stroke events in their investigation of sinus rhythm management, and provided an estimate of the hazard of stroke for AF relative to NSR 14. Using a Cox proportional hazards regression analysis, the presence of AF was found to be significantly associated with a 60% increase in the risk of stroke after adjusting for several covariates including the use of warfarin therapy.…”
Section: Methodsmentioning
confidence: 99%
“…A separate search of the literature was undertaken to identify additional evidence related to the prognostic value of NSR in patients with AF. The search identified an analysis of the AFFIRM study, which examined the occurrence and characteristics of stroke events in their investigation of sinus rhythm management, and provided an estimate of the hazard of stroke for AF relative to NSR 14. Using a Cox proportional hazards regression analysis, the presence of AF was found to be significantly associated with a 60% increase in the risk of stroke after adjusting for several covariates including the use of warfarin therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Despite evidence that people in AF are at an increased risk of stroke,3 large randomised controlled studies (including the AFFIRM trial)7 observed rate and rhythm control using drugs to be equivalent in terms of mortality 7 8. This can largely be attributed to the poor efficacy and harmful side effects of antiarrhythmic drugs (AADs) 9.…”
Section: Rate or Rhythm Control?mentioning
confidence: 99%
“…As asymptomatic AF is common, the worse outcome in the rhythm control groups may be attributed to occult AF and ischaemic strokes occurring in patients where anticoagulation had been discontinued 3. A recent study was performed with 2580 participants with either pacemakers or implantable cardiac defibrillators in whom asymptomatic AF burden could be accurately assessed by the device.…”
Section: Rate or Rhythm Control?mentioning
confidence: 99%
See 1 more Smart Citation
“…36 Even in patients after cardioversion, thromboembolic events occur after the anticoagulation is stopped or is subtherapeutic. 37 Thus, in patients with persistent atrial fibrillation, anticoagulation should be considered long term in those who are at risk of recurrence of atrial fibrillation or in those who have stroke risk factors.…”
Section: Persistent and Paroxsymal Atrial Fibrillationmentioning
confidence: 99%